On the Question of the Attitude to Sports Practices in Orthodoxy - A. S. Gonashvili (Дискурс, 2023)
Introduction.  The  article   is  aimed   at  a  comprehensive  and  holistic  analysis  of  the judgments  existing in Orthodox circles regarding physical culture and sports, reflecting the Orthodox   worldview and  its  values.  The  novelty  of  the   article   lies  in  the   empirical substantiation of the  role of the  physical and spiritual development  of believers  against the  background  of sports  practices,  as  well as  the  substantiation of contradictions  and problems  of perception,  sports practices  in the conditions of the Orthodox worldview. Methodology and  sources. A  comprehensive  approach  to the  problem  of studying and analyzing sports practices  is used as a methodological  basis. The main research method  in the work is an Internet survey.Results and discussion. According  to the  study, it should be  noted  that  there  is no unity among Orthodox people in understanding  the role of physical culture in Orthodox spiritual development.  Most people believe that the call for the development  of their body is not the work of the church, they do not see  any sin in the underdevelopment of their body. This is the  result  of the  influence  of various values  that  are  in one  or another  society  in which people  live. Therefore,  it is especially important  to emphasize  the role of the church in the educational process  of physical culture among young people and the younger generation.Conclusion. In general,  the author  of the article comes  to the conclusion  that there  is no unity among  Orthodox  people  in understanding  the  role of physical culture  in Orthodox spiritual development.